388 RESIDENTS AS TEACHERS AND LEADERS: RESULTS OF A NEEDS ASSESSMENT. Issue 1 (1st January 2007) - Dewey, C. M.; Ismail, N. J.; Tejada-Simon, M. V.; Turner, T. L.; Culberson, J. W.; Coverdale, J. H.; Patton, C. S.; Thompson, B. M.; Friedland, J. A.
Abstract : Purpose: The purpose is to create a resident as teachers and leaders program (RATL) for our institution using the best available evidence by conducting a complete needs assessment. Methods: A thorough needs assessment consisting of literature reviews, surveys, focus groups, nominal group techniques, and reviews of accrediting organizations' recommendations on residents' teaching skills was done. Results: The LCME clearly emphasizes residents teaching skills and the need to implement programs as outlined in ED-24. The literature supported the contention that students spend more time with residents than attending physicians. Student survey results report high amounts of self-learning (50-75%), which mirrors previous reports in the literature. Students felt that residents had a limited teaching ability for systems-based practice and listing differential diagnoses. In general, residents needed improvement in linking basic to clinical sciences, teaching differential diagnosis, presentation skills, and teaching physical exam skills. Fifty-seven percent of students felt that they witnessed an outstanding faculty teacher on a daily basis compared with an outstanding resident teacher (38%). Students felt that residents and faculty should teach slightly different topics. Most residents spend between 26 and 50% of their time teaching students, and only 45% had any training to enhance their teaching skills. Up to 55% of residents were not aware of student learning objectives. Using a 5-point Likert scale, residents ranked their level of confidence highest for teaching the following: demonstrating team dynamics/teamwork (mean = 3.90/SD = 0.80), teaching/demonstrating history taking skills (mean = 3.86/SD = 0.65), professionalism (mean = 3.88/SD = 0.78), and differentiating stable from acute patients (mean = 3.63/SD=0.60). They ranked teaching evidence-based medicine lowest at a mean of 2.6 (SD = 0.98). Residents want further teaching on dealing with problem students (38.8%), bedside teaching (36.7%), giving lectures (32.7%), and writing student evaluations (30.6%). The nominal group technique identified key content areas to include in a teaching session and formatting issues for computer-based learning tools. Conclusions: Using various sources for the needs assessment helped ensure that all sources were included before making decisions on program development and implementation. Each source provided information important to development of the program.